6-Gingerol Alleviates Neonatal Hypoxic-Ischemic Cerebral and White Matter Injury and Contributes to Functional Recovery - Zhao, Man; Yao, Yuan; Du, Jingyi; Kong, Liang; Zhao, Tiantian; Wu, Dong; Man, Lajie; Zhou, Wenjuan (Frontiers in Pharmacology, 2021)
Hypoxic-ischemic encephalopathy (HIE) is the main cause of neonatal death and disability with substantial injury of white and gray matter, which can lead to severe neurobehavioral dysfunction, including intellectual disability and dyskinesia. Inflammation, nerve cell death and white matter injury are important factors in the pathological process of HIE. 6-gingerol is a ginger extract, which has been shown to reduce inflammatory response and cell death. However, the role of 6-gingerol in neonatal HIE remains unknown. Here, we found that 6-gingerol treatment can alleviate HIE-induced brain damage and improve short-term reflexes, which were closely related to cell death and neuroinflammation. In addition, 6-gingerol could reduce neuronal apoptosis and pro-inflammatory factor release as well as microglia activation. Furthermore, 6-gingerol significantly improved motor ability, which was associated with white matter damage. Accordingly, our results showed that 6-gingerol can reduce the loss of myelin sheath, alleviate the cell death of oligodendrocytes, and stimulate the maturation of oligodendrocytes. In terms of mechanism, we found that 6-gingerol can decrease the level of Histone H3K27me3 at 3 days post HIE. Meanwhile, it can activate the AKT pathway and inhibit the activation of ERK and NF-B pathway at 3 days post HIE. Taken together, our data clearly indicate that 6-gingerol plays a neuroprotective role in HIE by epigenetic modification and regulation of AKT, ERK and NF-B pathways to inhibit inflammatory reaction and reduce cell death.